There's no place like space! - Rabe, Tish; Ruiz, Aristides (New York : Random House, 1999)
Dr. Seuss's Cat in the Hat introduces Sally and Dick to the planets, stars, and moons in our universe.
Includes bibliographical references (page 43) and index.
Keywords: Astronomy -- Juvenile literature